2017
DOI: 10.1038/onc.2017.401
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PPARα by clofibrate sensitizes pancreatic cancer cells to radiation through the Wnt/β-catenin pathway

Abstract: Radiotherapy is emerging as an important modality for the local control of pancreatic cancer, but pancreatic cancer cell radioresistance remains a serious concern. Peroxisome proliferator-activated receptor α (PPARα) is a member of the PPAR nuclear hormone receptor superfamily, which can be activated by fibrate ligands. The clinical relevance of PPARα and its biological function in pancreatic cancer radiosensitivity have not been previously described. In this study, we examined PPARα expression in tissue sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…Recently, several studies have shown the participation of Wnt6, Barx1, ptprz1, and other genes in the regulation of Wnt/β-catenin signalling and their involvement in the development of malignant tumours [31][32][33][34][35][36][37][38][39][40][41]. These ndings support our hypothesis that dlx6-as1 may affect the mRNA expression of Wnt6, Barx1, ptprz1 and other genes through ceRNA network to regulate Wnt/β-catenin signalling and participate in the distant bone metastasis of breast cancer.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, several studies have shown the participation of Wnt6, Barx1, ptprz1, and other genes in the regulation of Wnt/β-catenin signalling and their involvement in the development of malignant tumours [31][32][33][34][35][36][37][38][39][40][41]. These ndings support our hypothesis that dlx6-as1 may affect the mRNA expression of Wnt6, Barx1, ptprz1 and other genes through ceRNA network to regulate Wnt/β-catenin signalling and participate in the distant bone metastasis of breast cancer.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the LXXLL motif and mass spectrographic analysis of CLPTM1L revealed a potential ability of CLPTM1L to interact with many other nuclear receptors, such as RXRα, RXRβ and PPARα. It has been reported that the nuclear receptors are involved in modulating the radiosensitivity of cancer cells during radiotherapy [94][95][96]. Above all, our results reveal a new character of CLPTM1L, which functions in the nucleus through interacting with nuclear receptors during NSCLC radiotherapy.…”
Section: Discussionsupporting
confidence: 56%
“…Ptprz1 is included in the yellowgreen module and is expressed >10-times higher in δ-cells than α-cells or β-cells (DIGRUCCIO et al 2016), consistent with it playing a key role δ-cells. Ptprz1 is a receptor for the heparin-binding glycoprotein pleiotrophin (PTN), and has been associated with several cancers, including glioblastoma (SHI et al 2017), and pancreatic cancer (XUE et al 2017). In addition to δ-cell-specific transcripts, six genes that encode Ca 2+ -channels were included in the yellowgreen module, including R-type Ca 2+ channels (e.g., Cacna1e), which have been previously linked to glucose-stimulated somatostatin secretion (ZHANG et al 2007).…”
Section: Discussionmentioning
confidence: 99%